Stochastic reverse logistics network design for waste of electrical and electronic equipment - Ayvaz, Berk; Bolat, Bersam; Aydin, Nezir (ELSEVIER, 2015)
In recent years, Reverse Logistics has received increasing attentions in supply chain management area. The reasons such as political, economic, green image and social responsibility etc. force firms to develop strategies to their current systems. The aim of this study is to propose a generic Reverse Logistics Network Design model under return quantity, sorting ratio (quality), and transportation cost uncertainties. We present a generic multi-echelon, multi-product and capacity constrained two stage stochastic programing model to take into consideration uncertainties in Reverse Logistics Network Design for a third party waste of electrical and electronic equipment recycling companies to maximize profit. We validated developed model by applying to a real world case study for waste of electrical and electronic equipment recycling firm in Turkey. Sample average approximation method was used to solve the model. Results show that the developed two stage stochastic programming model provides acceptable solutions to make efficient decisions under quantity, quality and transportation cost uncertainties. (C) 2015 Published by Elsevier B.V.
Keywords: Reverse Logistics Network Design; Waste of electrical and electronic equipment (WEEE); Stochastic programming; Sample average approximation; Uncertainty; OPTIMIZATION MODEL; CONFIDENCE-INTERVALS; LOCATION MODEL; QUALITY; ROBUST; FLOWS; PAPER; Engineering; Environmental Sciences & Ecology